Spatiotemporal predictions of the alternative prey hypothesis: Predator habitat use during decreasing prey abundance. Issue 1 (26th January 2023) - Brunet, Mitchell J.; Monteith, Kevin L.; Huggler, Katey S.; Thompson, Daniel J.; Burke, Patrick W.; Zornes, Mark; Lionberger, Patrick; Valdez, Miguel; Holbrook, Joseph D.
Abstract: The alternative prey hypothesis supposes that predators supported by a primary prey species will shift to consume alternative prey during a decrease in primary prey abundance. The hypothesis implies that during declines of one prey species, a predator modifies their behavior to exploit a secondary, or alternative, species. Despite occurring in many systems, the behavioral mechanisms (e.g., habitat selection) allowing predators to shift toward alternative prey during declines in the abundance of their primary prey are poorly understood. We evaluated habitat selection and use by a generalist predator with respect to two prey species during a dramatic decrease in the abundance of primary prey. Further, we evaluated how spatial variation in access to primary prey affected habitat selection, and assessed similarity and overlap between habitats used by each prey species. Coyotes ( Canis latrans ) exhibited decreasing selection for cottontail rabbits ( Sylvilagus spp.; primary prey) during population decreases but did not shift habitat selection toward neonate mule deer ( Odocoileus hemionus ; alternative prey). Use of rabbit habitat remained high even during historically low rabbit abundance, while mule deer habitat was used in proportion to its availability. Coyotes seemingly do not make large shifts in habitat selection toward alternative prey following spatial and temporal decreases in the abundance of primary prey, but instead, take advantage of habitat overlap to facilitate prey‐switching behavior. Our work extends previous research conducted under the alternative prey hypothesis by explicitly evaluating the influence of habitat overlap between prey species and variation in access to prey habitat as factors affecting prey‐switching behaviors in predators.